"Let׳s do it ourselves" Individual motivations for investing in renewables at community level. (September 2015) - Dóci, Gabriella; Vasileiadou, Eleftheria
Abstract: Renewable energy communities have multiplied the last years in many countries, even in contexts that the structural conditions are not favorable. The paper analyses individual motivations for partaking in local renewable projects and generating energy jointly in an investment community, in order to inform policy debates on how to support such communities. To do so, we applied a socio-psychological approach for studying renewable energy communities in Germany and the Netherlands. Our results show that mainly gain (such as decreasing energy costs) and normative (such as addressing climate change) considerations played a role in the decision, but in the background hedonic motivations were also present, such as having fun and integrating in a community. Each of the groups examined emerged in already existing strong communities, where trust was relatively high, which seems to be an important condition for the realization of local energy projects. Consequently, we argue that tailor-made incentives addressing the different types of motivations can be more effective for the support and spread of renewable energy communities.